Na ile innowacyjny jest eksport usług z Polski? - Czarny, Elżbieta; Kuźnar, Andżelika; Śledziewska , Katarzyna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
We analyse Polish export of services, examining how innovative it is. We examine both the changes in the size of Polish exports of services as well as the importance of branches and geographical directions. We stress the relatively small economic and, consequently, export potential of Poland, as compared to the EU and the USA. At the same time, similar potentials of the EU and the USA, and different geographic distances and characteristics of their connections with Poland were the reason for comparing Poland’s exports to both partners. To analyse Poland’s total export of services, we add to the two previously mentioned trade partners a third group, which consists of relatively less developed countries. Consequently, the recipients of services from Poland are divided into the European Union, the United States and other trading partners defined as non-EU markets minus the USA. Due to absence of data and limited research framework, we limit the overall analysis to the years 2004-2013, while the detailed (industry) analysis to the years 2004-2012. In either case, the last year of the survey is also the last year for which annual Eurostat data is available.